Zoogeographic knowledge in the Ancient world - Andrey Aleksandrovich Likhovid; Arsen Oganesovich Berberyan; Evgeny Georgievich Mishvelov; Alina Igorevna Serdyukova (Наука. Инновации. Технологии, 2022)
This article raises the problem of the development of zoogeographical knowledge in the ancient East and Antiquity societies. As regards the analysis of knowledge of bio-geocenosis in the Ancient East, the images and descriptions of hieroglyphs, frescoes, tombs, figurines, etc., as well as folklore pieces were referred to. The authors found that the "biogenocenotic" theme was in demand in ancient Egypt. Generally, the scenic monuments reflected the scenes of hunting and economic activity. Based on the materials studied, it is concluded that in ancient Egypt there was Ancient Greek and Roman heritage which demonstrated attempts to systematize data on flora and fauna. The analysis of the works by Herodotus revealed the author's attempts to explain the numerical ratio of animals of different species in nature. Aristotle's works on zoogeography became an outstanding fact. A number of his researches are relevant in our time. The value of the information provided by ancient authors is based on their mobility. While traveling, they not only accumulated information about the fauna and population of animals in different territories, but made comparative geographical generalizations. The conclusions emphasize the following features: increasing knowledge of geography, compiling data on a larger number of systematic groups of animals, synchronism in the development of "biogeocenotic" views in the context of different cultures.